Characterization of 17 strains belonging to the Mycobacterium simiae complex and description of Mycobacterium paraense sp. nov - Fusco da Costa, Ana R; Fedrizzi, Tarcisio; Lopes, Maria L; Pecorari, Monica; Oliveira da Costa, Wana L; Giacobazzi, Elisabetta; da Costa Bahia, Jeann R; De Sanctis, Veronica; Batista Lima, Karla V; Bertorelli, Roberto; Grottola, Antonella; Fabio, Anna; et al. (International journal of systematic and evolutionary microbiology, 2015)
Fourteen mycobacterial strains isolated from pulmonary samples of independent patients in the state of Pará (Brazil), and three strains isolated in Italy, were characterized using a polyphasic approach. Thorough genetic investigation, including whole-genome sequencing, demonstrated that the strains belong to the M. simiae complex, being most closely related to Mycobacterium interjectum . For 14 of the strains, evidence emerged supporting their inclusion in a previously unreported species of the genus Mycobacterium , for which the name Mycobacterium paraense sp. nov. is proposed (type strain, IEC26 ᵀ = DSM 46749 ᵀ = CCUG 66121 ᵀ). The novel species is characterized by slow growth, unpigmented or pale yellow scotochromogenic colonies, and a HPLC mycolic acid profile different from other known mycobacteria. In different genetic regions, high sequence microheterogeneity was detected.